2018
DOI: 10.1136/bjophthalmol-2018-312209
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery refractive outcomes: representative standards in a National Health Service setting

Abstract: Refractive outcomes following routine cataract surgery reported here are well within the targets recommended by the Royal College of Ophthalmologists and European guidelines, but suggest that higher cataract refractive outcome benchmark standards may not yet be a realistic expectation for all NHS units with current biometry practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
(16 reference statements)
3
28
1
Order By: Relevance
“…Between 1 and 3 months, 46% of patients had SEs within 0.25 D, 80% within 0.50 D, and 95% within 1.00 D of the target. These values exceed the benchmark standards set by the UK National Health Service of 55% within 0.50 D and 85% within 1.00 D 28,29. Additionally, these results meet the new benchmark of 94% within 1.00 D of the target proposed by Massachusetts Eye and Ear 30.…”
Section: Discussionmentioning
confidence: 45%
“…Between 1 and 3 months, 46% of patients had SEs within 0.25 D, 80% within 0.50 D, and 95% within 1.00 D of the target. These values exceed the benchmark standards set by the UK National Health Service of 55% within 0.50 D and 85% within 1.00 D 28,29. Additionally, these results meet the new benchmark of 94% within 1.00 D of the target proposed by Massachusetts Eye and Ear 30.…”
Section: Discussionmentioning
confidence: 45%
“…National Health Service data suggested that 62.3% of patients within 0.5D of the refractive target should represent a minimum level of efficiency following cataract surgery. 23 Although this possibly represents the lower end of achievable accuracy, we compare favourably despite the higher potential risk profile of cataract surgery in cases with long-standing glaucoma. Vector astigmatic analysis suggested minor improvements although this may have been ameliorated by the relatively low preoperative refractive astigmatic values of our cohort (mean −0.91 ± 0.76D).…”
Section: Discussionmentioning
confidence: 91%
“…As regards refractive outcomes, our results also compare favorably with the recent reports. Mean absolute error between target and postoperative spherical equivalent was [21], and the EUROQUO report on refractive outcomes including surgeries performed in 2014 and 2015 found a mean absolute biometry prediction error of 0.42 D (SD 0.52) and 72.7% of eyes within 0.5 D of target [7]. Patients implanted with multifocal IOLs expect to be spectacle independent, and in order to achieve this and to optimize IOL performance, postoperative refraction should be close to emmetropia.…”
Section: Discussionmentioning
confidence: 99%